Resistance breeding in root and tuber crops at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria - Hahn, S.; Isoba, J.; Ikotun, T. (Elsevier, 1989)
Despite the advantages of root crops as important staple food crops in the tropics, research and development of such crops has been neglected. There is, therefore, the need for production, processing and utilization techniques to be developed, evaluated and made available to farmers. However, because of the limitations associated with the use of chemicals in Africa, development of resistant cultivars is the most appropriate and realistic approach to the control of pests and diseases. The strategy employed by IITA in breeding root and tuber crops resistant to diseases and pests is, first to identify the factors determining the incidence of such diseases and pests; these are the biological and environmental factors on which screening breeding materials in the field is based. The second step is to examine the factors influencing the efficiency of screening. Finally, the role of pathogenic variation in developing efficient and foolproof screening methods is examined. These form the basis of screening breeding materials for resistance to pests and diseases. Using this strategy, IITA has made substantial progress in breeding for resistance to cassava mosaic virus, cassava bacterial blight, the cassava mealybug, the cassava green spider mite, the African sweet potato weevils, the sweet potato virus disease complex, white yam scorch, cocoyam blight and nematodes.